2017
DOI: 10.1039/c7an00083a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the interactions between methylene blue and intramolecular G-quadruplexes: an explicit distinction in electrochemical behavior

Abstract: G-quadruplex sequences exist in eukaryotic organisms and prokaryotes, and the investigation of interactions between Gquadruplexes and small molecule ligands is important for gene therapy, biosensor fabrication, fluorescence imaging and so on. Here, we investigated the behaviour of methylene blue (MB), an electroactive molecule, in the presence of different intramolecular G-quadruplexes by electrochemical method using a miniaturized electrochemical device based on its intrinsic electrochemical property. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…59 These upfield shifts associated with 1 H signals of MB in gels (i.e., Dd = 0.3, 0.3 and 0.7 ppm for the signals at 7.7, 6.8 and 6.2 ppm, respectively) can be attributed to the p-p stacking and CH-p interactions that occur between MB and G4 fibrils. In addition, various binding interactions, such as end stacking, side stacking and parallel stacking of MB molecules to G4-rich DNA, have been previously proposed, 55 and those same types of interactions may be relevant here in the context of MB binding to the G4ÁK + gels. Also, a priori, ionic interactions between cationic MB and borate anions in the G4ÁK + borate gels are certainly important.…”
Section: Roles Of Cations and Borate Anions In The Gelation Of G-boramentioning
confidence: 83%
See 1 more Smart Citation
“…59 These upfield shifts associated with 1 H signals of MB in gels (i.e., Dd = 0.3, 0.3 and 0.7 ppm for the signals at 7.7, 6.8 and 6.2 ppm, respectively) can be attributed to the p-p stacking and CH-p interactions that occur between MB and G4 fibrils. In addition, various binding interactions, such as end stacking, side stacking and parallel stacking of MB molecules to G4-rich DNA, have been previously proposed, 55 and those same types of interactions may be relevant here in the context of MB binding to the G4ÁK + gels. Also, a priori, ionic interactions between cationic MB and borate anions in the G4ÁK + borate gels are certainly important.…”
Section: Roles Of Cations and Borate Anions In The Gelation Of G-boramentioning
confidence: 83%
“…The cationic and planar dye, methylene blue (MB), is well known to bind to G-quadruplex DNA fibrils. [54][55][56][57] We have previously studied the physical absorption of MB by these anionic GB gels, using both UV-Vis spectroscopy and 11 B NMR spectroscopy. 21,22 In particular, we found that G4ÁK + gels (72 mM in G) were able to quantitatively absorb 12.5 mM MB after soaking the hydrogel in a KCl solution of the dye for 24 h, as determined by UV-Vis spectroscopy.…”
Section: Roles Of Cations and Borate Anions In The Gelation Of G-boramentioning
confidence: 99%
“…However, further investigation in infected cells is required to assess whether berberine effectively reduces SARS-CoV-2 infectivity. Methylene blue (M-Blue), a tricyclic phenothiazine compound, has been shown to have G4-stabilizing properties [255]. M-Blue has been previously approved by the FDA for the treatment of methemoglobinemia and other medical applications [256].…”
Section: Coronavirusesmentioning
confidence: 99%
“…For example, the hemin/G4, a known horseradish peroxidase mimicking DNAzyme, has been widely used in the construction of various electrochemical biosensors ( Wu et al, 2017 ; Liu et al, 2017b ; Chen et al, 2018 ; Sun et al, 2018 ; Ji et al, 2019 ; Wu et al, 2021a ). The discovery that the combination of G4 and MB can cause a great reduction in MB diffusion current has further expanded its biosensing application scope ( Zhang et al, 2014 ; Cao et al, 2017 ; Zhao et al, 2020b ). Subsequently, it was found that G-triplex (G3), as a folding intermediate of G4, has an even stronger affinity to MB than G4.…”
Section: Introductionmentioning
confidence: 99%